Efficacy of Ranibizumab in Eyes with Diabetic Macular Edema and Macular Nonperfusion in RIDE and RISE - Reddy, Rahul K.; Pieramici, Dante J.; Gune, Shamika; Ghanekar, Avanti; Lu, Na; Quezada-Ruiz, Carlos; Baumal, Caroline R. (Ophthalmology (Rochester, Minn.), 2018)
To determine whether there are baseline characteristics that distinguish patients with diabetic macular edema (DME) with coexisting macular nonperfusion (MNP) at baseline and assess these patients’ potential to achieve favorable visual acuity (VA), anatomic, and diabetic retinopathy (DR) outcomes over 24 months. Post hoc analysis of RIDE/RISE, 2 phase 3, parallel, randomized, multicenter, double-masked trials (ClinicalTrials.gov: NCT00473382; NCT00473330). Study eyes with best-corrected VA (BCVA)/fluorescein angiogram (FA) data at baseline. To measure MNP, the Early Treatment for Diabetic Retinopathy Study (ETDRS) grid was overlaid on FAs of the macula. The MNP area was calculated by estimating the percentage of capillary loss in the central, inner, and outer subfields and converting into disc areas (DAs) using a software algorithm. Summary statistics and P values, respectively, were provided for all outcomes and comparisons of interest. Baseline characteristics; MNP area, BCVA, and central subfield thickness (CST) at months 12 and 24; and incidence of study eyes with ≥2-step DR improvement at months 3, 6, 12, 18, and 24. Baseline MNP was detected in 28.2%, 25.8%, and 26.3% of study eyes in the ranibizumab 0.3 mg (n = 213), ranibizumab 0.5 mg (n = 225), and sham (n = 228) arms, respectively. At baseline, patients with MNP were younger and had shorter diabetes duration, worse vision, increased CST, and worse DR severity (P values < 0.01 vs. those without MNP). In the ranibizumab 0.3 mg arm, eyes with baseline MNP had lower mean baseline BCVA (53.4 vs. 57.2 ETDRS letters for those without baseline MNP; P = 0.05), but mean BCVA gain at month 24 was comparable (+15.6 vs. +13.4 ETDRS letters, respectively; P = 0.2). Eyes with baseline MNP had increased CST at baseline, but experienced a greater decrease in CST by month 24. The proportion of eyes with ≥2-step DR improvement was greater for eyes with versus without baseline MNP in each ranibizumab arm. Despite having worse vision/increased CST versus those without baseline MNP, eyes with concurrent DME and baseline MNP entering RIDE/RISE experienced robust VA and anatomic improvement with ranibizumab and therefore should not be excluded from therapy.